2018
DOI: 10.1177/1120672118784802
|View full text |Cite
|
Sign up to set email alerts
|

The fate of abstracts presented at international ophthalmology meetings: 2- and 5-year publication rates

Abstract: Less than half of abstracts presented at the major ophthalmology meetings reach publication within 5 years of their initial presentation. Professionals attending meetings may consider adopting a more critical approach to the preliminary results reported in presented abstracts. Increasing publication rates and reducing potential publication bias is of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…This analysis demonstrated that when compared to other academic specialty research conferences, although time to publication was relatively consistent, the percentage of presented research going on towards publication was relatively low. Publication rates in other fields have ranged from 30% on the low end to 70% on the higher end, with podium presentations generally resulting in higher rates of publication (Lehman et al, 2017; see also Rushing et al, 2018; see also Marsland, Mumith, & Taylor, 2018; Villani et al, 2019; Ohtori et al, 2018; Miguel‐Dasit et al, 2005; Narain et al, 2017; Lloyd, et al, 2006; Chan & Graham, 2010; Amirhamzeh et al, 2012; Gregory & Liu, 2012; Tyagi et al, 2013). The overall publication rate from CUGH and GHIC from 2014 to 2015 was 34.0%; in contrast, the Arthroscopy Association of North America Annual Meetings were determined to have an overall podium presentation publication rate of 67.3% (Lehman et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This analysis demonstrated that when compared to other academic specialty research conferences, although time to publication was relatively consistent, the percentage of presented research going on towards publication was relatively low. Publication rates in other fields have ranged from 30% on the low end to 70% on the higher end, with podium presentations generally resulting in higher rates of publication (Lehman et al, 2017; see also Rushing et al, 2018; see also Marsland, Mumith, & Taylor, 2018; Villani et al, 2019; Ohtori et al, 2018; Miguel‐Dasit et al, 2005; Narain et al, 2017; Lloyd, et al, 2006; Chan & Graham, 2010; Amirhamzeh et al, 2012; Gregory & Liu, 2012; Tyagi et al, 2013). The overall publication rate from CUGH and GHIC from 2014 to 2015 was 34.0%; in contrast, the Arthroscopy Association of North America Annual Meetings were determined to have an overall podium presentation publication rate of 67.3% (Lehman et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Low priority of publication and expecting journal rejection were other notable reasons given by authors for not publishing (Scherer, Ugarte‐Gil, Schmucker, & Meerpohl, 2015). The studies that we looked at listed other notable factors, including a lack of institutional support for individuals (especially students) seeking to publish and the educational versus publication value of conference abstracts (Rushing et al, 2018; see also Marsland, Mumith, & Taylor, 2018; Villani et al, 2019; Ohtori et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, a full publication was required to have an author list, including at least the first and last authors of the presentation, a title, including the related keywords as the abstract title, and apparently reproduce the material and methods of the presentation. Publications with different sample sizes (compared to the abstract) were accepted as a match if the aim of the study and methods were the same as the abstract and the author criteria were compatible (15,16). If publications could not be reached, the most appropriate keywords for the presentation were selected, and all publications by the first/final author between the congress date and 2020 were searched again.…”
Section: Methodsmentioning
confidence: 99%